2017
DOI: 10.1186/s12882-017-0525-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the long-term outcomes of idiopathic membranous nephropathy

Abstract: BackgroundWe attempted to describe the clinical features and determine the factors associated with renal survival in idiopathic membranous nephropathy (iMN) patients with nephrotic syndrome (NS) and to determine the factors associated with spontaneous complete remission (sCR) and progression to NS in iMN patients with subnephrotic proteinuria.MethodsThis retrospective study involved 166 iMN patients with NS and 65 patients with subnephrotic proteinuria. The primary end point was a doubling of serum creatinine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 23 publications
3
26
0
Order By: Relevance
“…iMN is a multifactorial disease, which interactions between many factors including age, gender, and so on. [ 21 ] But data for people of different age and gender were limited, and data were not available to perform subgroup analyses based on age or gender. Anyway, our result indicated that HLA-DQA1 gene polymorphism was associated with iMN risk.…”
Section: Discussionmentioning
confidence: 99%
“…iMN is a multifactorial disease, which interactions between many factors including age, gender, and so on. [ 21 ] But data for people of different age and gender were limited, and data were not available to perform subgroup analyses based on age or gender. Anyway, our result indicated that HLA-DQA1 gene polymorphism was associated with iMN risk.…”
Section: Discussionmentioning
confidence: 99%
“…Since the clinical features and prognosis of IMN are variable, the disease has a high rate of spontaneous remission. Spontaneous complete remission (CR) of proteinuria is observed after a variable period of time (4–120 months) in approximately 30%–40% of adult patients 2 3. Despite this, 30%–40% of patients progress toward end-stage renal failure within 5–15 years 4…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, a multivariate Cox proportional hazards regression analysis was performed to investigate the association of DBP with renal outcomes. A previous study showed that patients with IMN suffered from CKD as a result of hypertension, and that hypertension was secondary to renal disease (18). Therefore, monitoring BP during diagnosis in patients with IMN may facilitate prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the present study identified that Scr, LDL and 24 h urine protein were increased, and serum albumin and e-GFR were decreased in patients with IMN with hypertension. Huh et al (18) reported that low serum albumin levels at the onset of the disease were associated with poor renal prognosis of patients with IMN. Another previous study reported that high levels of Scr at diagnosis are major predictors of the progression of IMN to ESRD (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation